Pro Apache Geronimo - Kumar, Kishore (Apress : Imprint: Apress, 2006)
Pro Apache Geronimo teaches you all about using Apache Geronimo, the open-source lightweight J2EE/Java EE 5 web application server. Geronimo's GBeans enable you to deploy sophisticated server-side enterprise Java applications and perform special enterprise-level Java development for transactional support. Geronimo is unique in that it's the only open-source lightweight deployment tool around. It also has the capabilities for Spring compliance, so Spring developers can deploy their web applications using Geronimo. Meanwhile, JBoss is the only other significant open-source J2EE container out there. Geronimo, now backed by IBM, is incorporated into IBM's WebSphere Community Edition/Package. This book is a must-have because it: Is the first book to cover Apache Geronimo in such detail Features lots of code samples to learn from and apply to your work Explores relevant internals.